INDONESIA IN THE AMERICAN COMICBOOKS: A MIMESIS STUDY - Yudhy Purwanto; Neneng Yuniarty (Universitas Widyatama, 2023)
This research was aimed to know the forms of mimesis that are represented in the American comicbooks. The characters are mostly well-known fictional superheroes and active worldwide, but usually based in USA. The mimesis analysis was done by comparing some aspects in the real life and those in the comics. Those comparison aspects will be seen and examined to point out the true mimesis used by the writers and how Indonesia is pictured there. The mimesis theory was taken from Krofli? (2011). There, Indonesia was illustrated in three ways, i.e.: 1) by the picture; 2) by a character’s explanation; and 2) by both. The comparison aspects were divided into two parts, i.e.: 1) the condition of Indonesia when they were written; and 2) the plots and their conotative meanings. Those illustrations and comparisons resulted 3 different point of views, i.e., positive, negative, or neutral. There are 30 data analized and it resulted only 12 data with full mimesis similarities and 18 data with partly similarities or completely different mimesis with the real conditions. The other aspects analyzed was about their description of Indonesia as a whole, and it turns out that only 3 data that have positive vibes, 11 data say negative things about Indonesia, and the other 16 are neutral.